INVESTIGATING INFLUENCES OF SEA-LAND CIRCULATION ON OZONE POLLUTION IN SOUTHERN TAIWAN BY COUPLING CLUSTER ANALYSIS WITH BACK - TRAJECTORY SIMULATION - Lin, Kun-Ming; Yu, Tai-Yi; Chang, Len-Fu Walter (International journal of organizational innovation, 2014)
This study employs cluster analysis on the coordinate numbers of the back trajectories gathered from meteorological stations by choosing the Kao-Ping air quality basin, the most severely polluted air quality basin in Taiwan, as the subject. By analyzing the back trajectories of the 14 stations during spring and autumn (183 days in total), the authors realized the correlation between the categorization of back trajectories and ozone concentration. The results of cluster analysis indicated that the agglomeration employed by Ward's method works better than the average linkage method. The back trajectory routes consisted of four types, namely, slow monsoon, sea breeze, stagnation, and fast monsoon types. From the analytical results of the topology, weather, and back trajectories of the Kao-Ping air quality basin, the stations that contributed to the highest-concentration ozone pollution were mostly located in the coastal areas of Kaohsiung City, especially with the backward trajectory brought by the westerly sea breeze.